Be damned, and publish? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
'The old adage of 'Publish and be damned' could well be reversed in the case of many of those publishers met during the study [conducted by CTA on publishing activities in nine African countries in 1990 ed.]. In addition to the obstacles faced by...